2014
DOI: 10.3906/tar-1309-45
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient uptake of peanut genotypes with different levels of drought tolerance under midseason drought

Abstract: The objective of this study was to investigate the responses of peanut genotypes to midseason drought, regarding in particular nutrient uptakes and their correlations with biomass production and pod yield. The experiment was conducted during the dry seasons of 2011/12 and 2012/13. Five peanut genotypes with different levels of drought tolerance and 2 water regimes (well-watered and midseason drought) were laid out in a split-plot design with 4 replications. Midseason drought was imitated by stopping irrigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Significant positive correlations between SPAD (LCS, leaf color score measured six weeks after emergence) and nitrogen fixation (measured as nodule dry weight, NDW) in soybean suggested the use of SPAD as an indicator of SNF effectiveness in soybean (Gwata et al, 2004). In addition, Dinh et al (2013) identified significant positive correlations among SPAD (75 DAP), pod yield and fixed nitrogen (N-difference method) in Bradyrhizobium inoculated peanuts (five genotypes) under two water conditions. Moreover, relatively high heritability for SPAD estimated in maize (Korkovelos and Goulas, 2011) and confirmed in bean (Farid, 2015) suggested the use of SPAD as indirect measure in simultaneous selection for high yield and good ability for nitrogen fixation.…”
Section: Variability Of Nitrogen Fixation Measured As %Ndfa Exist Amomentioning
confidence: 94%
“…Significant positive correlations between SPAD (LCS, leaf color score measured six weeks after emergence) and nitrogen fixation (measured as nodule dry weight, NDW) in soybean suggested the use of SPAD as an indicator of SNF effectiveness in soybean (Gwata et al, 2004). In addition, Dinh et al (2013) identified significant positive correlations among SPAD (75 DAP), pod yield and fixed nitrogen (N-difference method) in Bradyrhizobium inoculated peanuts (five genotypes) under two water conditions. Moreover, relatively high heritability for SPAD estimated in maize (Korkovelos and Goulas, 2011) and confirmed in bean (Farid, 2015) suggested the use of SPAD as indirect measure in simultaneous selection for high yield and good ability for nitrogen fixation.…”
Section: Variability Of Nitrogen Fixation Measured As %Ndfa Exist Amomentioning
confidence: 94%
“…For the stress treatment (MD), irrigation was stopped during 30-60 DAP and resumed to FC at 60 DAP again until harvest. Irrigation needs were calculated as the sum of crop water requirements and soil evaporation (Sing and Russel, 1981;Doorenbos and Pruitt, 1992;Dinh et al, 2014) and applied daily to the appropriate plots. ), rainfall (mm), pan evaporation (mm), relative humidity (%), and minimum and maximum air temperature were recorded daily from planting to harvest using a nearby weather station.…”
Section: Irrigationmentioning
confidence: 99%
“…for genotypes,Arunyanark et al, (2009),Dinh et al (2013) andArruda et al (2015) for irrigation regimes andGirdthai et al (2010) andArunachalam & Kannan (2013) for genotype×irrigation interaction.…”
mentioning
confidence: 99%